Fine‐root traits are linked to species dynamics in a successional plant community. Issue 3 (21st February 2019) - Caplan, Joshua S.; Meiners, Scott J.; Flores‐Moreno, Habacuc; McCormack, M. Luke
Abstract: Despite the importance of fine roots for the acquisition of soil resources such as nitrogen and water, the study of linkages between traits and both population and community dynamics remains focused on aboveground traits. We address this gap by investigating associations between belowground traits and metrics of species dynamics. Our analysis included 85 species from a long‐term data set on the transition from old field to forest in eastern North America (the Buell‐Small Succession Study) and the new Fine‐Root Ecology Database. Given the prominent roles of life form (woody vs. non‐woody) and species origin (native vs. exotic) in defining functional relationships, we also assessed whether traits or their relationships with species dynamics differed for these groups. Species that reached their peak abundance early in succession had fine‐root traits corresponding to resource acquisitive strategies (i.e., they were thinner, less dense, and had higher nitrogen concentrations) while species that peaked progressively later had increasingly conservative strategies. In addition to having more acquisitive root traits than native species, exotics diverged from the above successional trend, having consistently thinner fine roots regardless of the community context. Species with more acquisitive fine‐root morphologies typically had faster rates of abundance increase and achieved their maximal rates in fewer years. Decreasing soil nutrient availability and increasing belowground competition may become increasingly strong filters in successional communities, acting on root traits to promote a transition from acquisitive to conservative foraging. However, disturbances that increase light and soil resource availability at local scales may allow acquisitive species, especially invasive exotics, to continue colonizing late into the community transition to forest.